2019
DOI: 10.1007/s10648-019-09492-2
|View full text |Cite
|
Sign up to set email alerts
|

Facilitating Diagnostic Competences in Higher Education—a Meta-Analysis in Medical and Teacher Education

Abstract: Facilitating diagnostic competences is an important objective of higher education for many professions. This meta-analysis of 35 empirical studies builds on a conceptual framework and investigates the role of problem-solving, scaffolding, and context to foster diagnostic competences in learners with lower and higher professional knowledge bases. A moderator analysis investigates which type of scaffolding is effective for different levels of learners' knowledge bases, as well as the role of the diagnostic conte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
88
3
22

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
4

Relationship

5
4

Authors

Journals

citations
Cited by 93 publications
(134 citation statements)
references
References 92 publications
6
88
3
22
Order By: Relevance
“…Before including less advanced learners medical educators should consider how to ensure that learners profit from VPs. One way to make VPs profitable for less advanced students could be as reflection prompts with instructional support adapted to the prior knowledge of learners [20] or even to incorporate other instructional methods before working on the VPs. While parts of the design for VPs are important to foster clinical reasoning, we found that testing students' actual subject-specific prior knowledge levels is also of great value.…”
Section: Discussionmentioning
confidence: 99%
“…Before including less advanced learners medical educators should consider how to ensure that learners profit from VPs. One way to make VPs profitable for less advanced students could be as reflection prompts with instructional support adapted to the prior knowledge of learners [20] or even to incorporate other instructional methods before working on the VPs. While parts of the design for VPs are important to foster clinical reasoning, we found that testing students' actual subject-specific prior knowledge levels is also of great value.…”
Section: Discussionmentioning
confidence: 99%
“…The promotion of SRL is best combined with the teaching of learning content (school subject) and is not an extracurricular activity. Providing guidance and direct instruction might be most effective for less advanced self-regulated learners, while scaffolding and high levels of autonomy might be more beneficial for advanced self-regulated learners (van de Pol et al, 2010;Chernikova et al, 2020). Consequently, considering differences between students becomes crucial for teachers' SRL instruction and support (Peeters et al, 2016).…”
Section: Teaching Self-regulated Learningmentioning
confidence: 99%
“…This implies a transfer from an externally regulated form of learning to a co-regulated form finally moving toward students' selfregulated forms of learning (van de Pol et al, 2010;van Beek et al, 2014). This highlights the important role of continuously diagnosing students SRL competences, which is achieved by coaching students and providing SRL related feedback (Hamman et al, 2000;Klug et al, 2013;Chernikova et al, 2020;Vattøy, 2020). However, several studies reported that teachers rarely integrate SRL in their everyday classroom instruction, provide little direct instruction of strategies, and seldomly emphasize metacognitive aspects of SRL (Kistner et al, 2015;Spruce and Bol, 2015;Karlen, 2016b;Dignath and Büttner, 2018;Zepeda et al, 2019).…”
Section: Teaching Self-regulated Learningmentioning
confidence: 99%
“…This meta-analysis summarizes the effects of scaffolding and technology use in simulation-based learning environments on facilitating a range of complex skills across domains (e.g., medical and teacher education, psychological counseling, care). In a previous meta-analysis, it has been found that the effects of instruction across domains of medical and teacher education have similar magnitude for a certain set of skills related to diagnosing; the effects increase in magnitude with the proper use of scaffolding (Chernikova et al, 2019). Other meta-analyses in the field of medical education (e.g., Cook, 2014) support the idea that simulations can be highly effective for advancing specific motor and technical skills.…”
mentioning
confidence: 99%